Efficacy of imipenem lavage versus saline lavage in perforation peritonitis - C. S., Santhosh; Singh, Avinash Chandra; Shetty, Karan K. (International Surgery Journal, 2018)
Background: Surgical treatment for perforation peritonitis is still believed to be demanding and complex in spite of the advent of better surgical technique, antimicrobial therapy and intensive care support improving the outcome of such cases. However, the specific details of the pre-operative, intra-operative and post-operative management have always been very controversial and debatable. This study aims to evaluate the efficacy of peritoneal cavity irrigation with imipenem solution in patients with perforation peritonitis and compare it with standard saline wash. Methods: This study was conducted in a tertiary care teaching hospital from November 2015 to April 2017 and included 90 patients aged between 12 and 60 years who are operated for perforation peritonitis. Patients are divided into 3 groups and underwent post laparotomy irrigation as follows saline and fluid drained, saline and then imipenem wash at a concentration of 1mg/ml and fluid drained after 5 minutes, saline and then imipenem wash at a concentration of 1 mg/ml and drain was clamped for 1 hour. The patients were then observed for post-operative complications. Results: There was a statistically significant reduction in post-operative wound infection (33.33%), intra-abdominal abscess (23.33%) and sepsis (23.33%) in group 3 when compared to other two groups. Group 3 had a much lower mortality rate (3.33%) when compared to the other two (16.67% and 6.67% respectively.) Conclusions: Addition of Imipenem to normal saline for intraoperative peritoneal lavage has much satisfactory post-operative outcome. Further studies with larger sample size are needed to accurately assess the statistical significance of the same.